2012
DOI: 10.1016/j.freeradbiomed.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of inducible nitric oxide synthase in mitochondrial depolarization and graft injury after transplantation of fatty livers

Abstract: This study investigated the role of inducible nitric oxide synthase (iNOS) in failure of ethanol-induced fatty liver grafts. Rat livers were explanted 20 h after gavaging with ethanol (5 g/kg) and storing in UW solution for 24 h before implantation. Hepatic Oil-Red-O staining-positive areas increased from ~2% to ~33% after ethanol treatment, indicating steatosis. iNOS expression increased ~8-fold after transplantation of lean grafts (LG) and 25-fold in fatty grafts (FG). Alanine aminotransferase release, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…Previous studies showed that one inebriating dose of ethanol causes overt steatosis (Zhong et al, 1997;Liu et al, 2012b). Consistent with these previous reports, livers from rats given saline revealed sparse distribution of small red fat droplets within hepatocytes (Fig.…”
Section: Acute Ethanol Treatment Causes Hepatic Steatosissupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies showed that one inebriating dose of ethanol causes overt steatosis (Zhong et al, 1997;Liu et al, 2012b). Consistent with these previous reports, livers from rats given saline revealed sparse distribution of small red fat droplets within hepatocytes (Fig.…”
Section: Acute Ethanol Treatment Causes Hepatic Steatosissupporting
confidence: 90%
“…RNS modify proteins thus altering their functions. Increased RNS formation is associated with more severe graft injury, poorer graft function and decreased survival (He et al, 2010;Shi et al, 2010;Liu et al, 2012b). Energy supply is essential for cell survival and function.…”
Section: Suramin and Transplantation Of Fatty Partial Liver Graftsmentioning
confidence: 99%
“…The role of RNS in MPT is controversial [8, 36, 37]. In this study we showed that iNOS was upregulated markedly in CDD grafts and that iNOS-deficiency blunted mitochondrial depolarization, ATP depletion, and injury in CDD grafts ( Figs.…”
Section: Discussionmentioning
confidence: 56%
“…However, one of the major mediators during intestinal inflammation process is iNOS [19][20][21]. Under various pathological conditions, iNOS is considered an important enzyme in the inflammatory response, leading to tissue injury by its multiple actions including apoptosis inducement, oxygen free-radical production, and mitochondrial injury effect [22][23][24]. Previous studies have shown that iNOS could mediate the intestinal inflammation, and lead to gastrointestinal dysmotility, while the iNOS inhibitor could reverse these effects in the gastrointestinal diseases [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the major mediators during intestinal inflammation process is inducible nitric oxide synthesis (iNOS) [19][20][21]. Under various conditions, iNOS is considered an important enzyme in the inflammatory response, leading to tissue injury by its multiple actions including apoptosis inducement, oxygen free-radical production, and mitochondrial injury effect [22][23][24]. However, it is still unknown if iNOS is involved in the intestinal inflammation after CKD progression.…”
Section: Introductionmentioning
confidence: 99%